Histological and immunohistochemical features of the ovarian malignant epithelial tumors and granulosa cell tumors - O. A. Savchenko; I. S. Shponka; V. R. Skoryk; P. V. Savchenko (Zaporozhye State Medical University, 2019)
Among cancers the ovarian cancer is one of the top ten in prevalence occupying the 7th place and one of the first five in mortality occupying the 4th place. These facts are explained, on the one hand, by the absence of specific clinical manifestations, which causes the diagnosis of the process at its later stages with a frequent metastatic lesion. On the other hand, there is a problem of reliable verification of the diagnosis. The purpose of the study is to improve the complex of differential diagnostic morphological criteria for malignant neoplasms of the ovaries verification, which is based on the latest international classifications and features of practical oncomorphology in Ukraine. Methods. Retrospective analysis of 115 malignant ovarian tumors (where 67 cases of different types carcinomas and 48 cases of granulosa cell tumor were included) contained assessment of histological, immunohistochemical characteristics followed by statistical processing of the results. Results. Received data made it possible to state the diagnostic value of each feature for the studied malignant tumors of the ovaries. Among the histological characteristics the most important were: macro- and micropapillas, follicular / glandular structures, polymorphism degree, mitotic activity, cell necrosis. Among the panel of immunohistochemical antibodies the fractions of cytokeratins (pancytoceratin AE1 / AE3, cytokeratin 7, cytokeratin 20), p53, WT-1, EMA and vimentin were mentioned. However, P > 0.05 for all the indicators. Conclusions. The necessity of using is based on a combination of histological criteria for a specific panel of IgG antibodies, which is statistically confirmed. Presence of papillary structures, mitotic activity, polymorphism and expression of p53 are clue for differentiation between HGSC and LGSC. Granulosa cell tumors had a special phenotype Vimentin + / Calretinin + / PanCK + (focally).